Alameda County (California) Health and Ways of Living Study, 1994 and 1995 Panels - Kaplan, George A. ([Verlag nicht ermittelbar], 2001)
This collection provides a 30-year follow-up with respondents from Alameda County who were originally interviewed in 1965 for the first wave of the Health and Ways of Living Study. The purpose of the survey was to explore the influences of health practices and social relationships on the physical and mental health of a typical sample of the population. The first wave of the study, HEALTH AND WAYS OF LIVING STUDY, 1965 PANEL: [ALAMEDA COUNTY, CALIFORNIA] (ICPSR 6688), collected information for 6,928 respondents (including approximately 500 women aged 65 years and older) on chronic health conditions, health behaviors, social involvements, and psychological characteristics. The second wave, the 1974 panel (ALAMEDA COUNTY [CALIFORNIA] HEALTH AND WAYS OF LIVING STUDY, 1974 PANEL [ICPSR 6838]), collected information from 4,864 of the original respondents. The third and fourth waves (1994 and 1995 panels, respectively), provided in this collection, explore some new topics. The third wave provides a follow-up of 2,729 original 1965 and 1974 respondents and examines health behaviors such as alcohol consumption and smoking habits, along with social activities. Also included is information on health conditions such as diabetes, osteoporosis, hormone replacement, and mental illness. Another central topic investigated is activities of daily living (including self-care such as dressing, eating, and shopping), along with use of free time and level of involvement in social, recreational, religious, and environmental groups. The fourth wave is a follow-up to the 1994 panel, and contains 2,569 cases. This wave examines changes in functional abilities such as self-care activities, employment, involvement in community activities, visiting friends/family, and use of free time since 1994.